Depositional Setting and Enrichment Mechanism of Organic Matter of Lower Cretaceous Shale in Ri-Qing-Wei Basin in the Central Sulu Orogenic Belt - Zhou, Tengfei; Zhou, Yaoqi; Zhao, Hanjie; Li, Manjie; Mu, Hongyu (Frontiers in Earth Science, 2022)
A suite of source rock consists of mudstone and shale, with great thickness and continuous deposition was found in the well LK-1 in Lingshan island in Ri-Qing-Wei basin. In order to evaluate the hydrocarbon generation prospects of these source rock and find the mechanism of organic matter enrichment, shale samples were selected from the core for TOC (total organic carbon) and element geochemistry analysis. The results show that organic matter abundance of the source rocks are generally high with average TOC content of 1.26 wt%, suggesting they are good source rocks. The geochemical features show that the sedimentary environment is mostly anoxic brackish water to salt water environment with arid to semiarid climate condition. The enrichment mechanism of organic matter varied with the evolution of the basin, which was divided into three stages according to the sedimentary characteristics. In the initial-middle period of rifting evolution (stage 1 and early stage 2), paleoproductivity is the major factor of OM-enrichment reflecting by high positive correlation between the TOC contents and paleoproductivity proxies. While with the evolution of the rift basin, redox condition and terrigenous clastic input became more and more important until they became the major factor of OM enrichment in the middle stage of rift evolution (stage 2). In the later stage of rift evolution (latest stage 2 and stage 3), besides terrigenous clastic input, the effect of paleoclimate on OM-enrichment increased gradually from a minor factor to a major factor.